PREVENTING DATA LOSS EVEN WHEN THE SECURITY SYSTEM COMPROMISE - S, Renu (Journal of Applied Engineering Science, 2018)
Storage as a service will diminish the risk of data storage but it leads to the era of data storage security. Studies show that multi cloud or inter cloud or clouds of cloud storage are eminent techniques which reduce the traditional risk of storage cloud. Replicating all data into numerous clouds will lead to monetary detriment as well as gigantic growth of electronic data. Inorder to overcome this horrible situation we have proposed a clouds tree to store files into multiple locations. Clouds tree is a hierarchical arrangement of public CSPs. There is no interconnection or configuration between CSPs but the relation is depends on file storage. The files which are more sensitive and capable to achieve business continuity are needed to store multiple locations. File splitting, encryption and storing different CSPs are the technique behind this work. Double or triple authentication schemes are provided to access sensitive or private data.